PEMBERDAYAAN PKK DALAM MENDORONG PROGRAM KETAHANAN PANGAN KELUARGA DI DESA MAUKELI - Adriana Maria Fouk; Mikhael Thomas Susu; Bruno Rey Sonby Pantola (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
ABSTRACT Family food security in Maukeli Village faces various challenges due to limited utilization of local resources and a lack of community participation, particularly among PKK members. This program aims to empower PKK women to become agents of change in supporting family food security by enhancing their skills in managing home gardens and processing agricultural products. A participatory approach was applied through direct training and mentoring in yard management and the development of economically valuable food products. The results of the activity show a significant improvement in the knowledge and awareness of PKK women in optimizing yard use, the realization of a sustainable family food security program, and an increase in family welfare through additional income. This empowerment reinforces the position of PKK as the frontline force in food security at the village level and promotes inclusive and independent village development.